Varför är det kvinnliga könet underrepresenterat vid Skogsmästarprogrammet? - Carlsson, Carl Johan (SLU/School for Forest Management, 2008)
The purpose of this work is to find out what female students think about Skogsmästarprogrammet (Forest Management – Bachelor's Programme) at the Swedish University of Agriculture. The programme has existed since 1945 and in total over the years 1974 - 2007 about 10 % females have been studying at the programme. Today 15 % of the students are women, and the goal is to reach at least 30 %. The central question in the present work is to investigate how it is possible to increase the proportion of women.